2021
DOI: 10.1038/s42255-021-00410-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated dietary ω-6 polyunsaturated fatty acids induce reversible peripheral nerve dysfunction that exacerbates comorbid pain conditions

Abstract: Chronic pain is the leading cause of disability worldwide 1 and commonly associated with comorbid disorders 2 . However, the role of diet in chronic pain is poorly understood. Of particular interest is the Western-style diet, enriched with ω-6 polyunsaturated fatty acids (PUFAs) that accumulate in membrane phospholipids and oxidize into pronociceptive oxylipins 3 , 4 . Here we report that mice administer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 93 publications
1
21
0
Order By: Relevance
“…Evidence to support this hypothesis was recently published by the laboratory of K.M. Hargeaves ( Boyd et al, 2021 ). Specifically, the authors observed that mice maintained on a diet with high ω-6 PUFA content displayed nociceptive hypersensitivities and C fiber hyper-responsivity when compared to animals maintained on a diet with low ω-6 PUFA content.…”
Section: Eicosanoid-transient Receptor Potential Interactions and Spi...mentioning
confidence: 82%
See 1 more Smart Citation
“…Evidence to support this hypothesis was recently published by the laboratory of K.M. Hargeaves ( Boyd et al, 2021 ). Specifically, the authors observed that mice maintained on a diet with high ω-6 PUFA content displayed nociceptive hypersensitivities and C fiber hyper-responsivity when compared to animals maintained on a diet with low ω-6 PUFA content.…”
Section: Eicosanoid-transient Receptor Potential Interactions and Spi...mentioning
confidence: 82%
“…Evidence to support this hypothesis was recently published by the laboratory of K.M. Hargeaves (Boyd et al, 2021). Specifically, the authors observed that mice maintained…”
Section: Eicosanoid-transient Receptor Potential Interactions and Spi...mentioning
confidence: 84%
“…Dynamic responses were assessed by stroking a cotton swab along the plantar surface of the rat’s hind paw, as described previously, with slight modifications [ 31 , 32 ]. The rats were acclimated for 30 min in the von Frey chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence also suggests that diet and metabolic factors influence the development and chronicity of pain symptoms. Diets containing high amounts of omega-6 fatty acids (common in Western diets) exacerbate nociceptive sensitivity in preclinical animal models of neuropathic and inflammatory pain ( Boyd et al, 2021 ). Importantly, Western diets appear to prolong recovery from a pain-related injury in animals, although recovery was accelerated by switching animals to an anti-inflammatory diet ( Totsch et al, 2018 ).…”
Section: Mechanisms Implicated In Alcohol-human Immunodeficiency Virus Interactions Increasing Risk and Pathogenesis Of Cardiometabolic Smentioning
confidence: 99%
“…Emerging evidence suggests that Western diets commonly consumed in the U.S. worsen both neurocognitive ( Martin and Davidson, 2014 ; Davidson et al, 2019 ) and pain symptomatology ( Boyd et al, 2021 ). Thus, the neurobiological interaction of excessive alcohol drinking, cognition, and pain in the context of WD consumption represents a critical area of research and public health interest.…”
Section: Mechanisms Implicated In Alcohol-human Immunodeficiency Virus Interactions Increasing Risk and Pathogenesis Of Cardiometabolic Smentioning
confidence: 99%